2009
DOI: 10.1016/j.carpath.2007.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Coronary atherosclerotic lesions in human immunodeficiency virus–infected patients: a histopathologic study

Abstract: Young to middle-aged patients dying from advanced AIDS have atherosclerotic CAD that may result in luminal narrowing, heavy calcification, and high plaque lipid content. The pattern of disease, location of lesions, and plaque composition are typical of atherosclerosis in HIV-negative patients. No relationship between antiretroviral therapies and atherosclerosis was seen in this small study of heavily treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…In addition, because it is known that a HIV-positive status is associated with cardiovascular effects, 29 eight younger and five older HIV-positive men were also excluded. By doing so, our associations not only remained consistent but were also strengthened (Table 4).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…In addition, because it is known that a HIV-positive status is associated with cardiovascular effects, 29 eight younger and five older HIV-positive men were also excluded. By doing so, our associations not only remained consistent but were also strengthened (Table 4).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Although the rise in cardiac disease frequency among HIV-infected individuals has been attributed to increased atherosclerotic burden, stroke mechanisms remain less well understood [2]. Stroke is a heterogeneous disease in which the mechanisms dictate natural history and, in some cases, also dictate the preventive measures to reduce the risk of recurrence [3].…”
mentioning
confidence: 99%
“…In a comparative histopathologic study of young deceased patients with end-stage HIV disease, Micheletti et al [25] demonstrated a greater burden of CAD and heavy coronary artery calcification in HIV-infected patients when compared to HIV-negative controls who died from other chronic illnesses. Two previously unreported patterns of dystrophic coronary calcification were described in both HIV-positive patients and older HIV-negative controls, suggesting coronary artery calcium might be a useful surrogate of the accelerated atherosclerotic process found in HIV patients [25].…”
Section: Coronary Artery Calcium Scoring and Coronary Ct Angiographymentioning
confidence: 98%